RADIOLOGY EDUCATION: A PILOT STUDY TO ASSESS KNOWLEDGE OF MEDICAL STUDENTS REGARDING IMAGING IN TRAUMA - Siddiqui, Saad; Saeed, Muhammad Anwar; Shah, Noreen; Nadeem, Naila (Journal of Ayub Medical College Abbottabad, 2015)
Background: Trauma remains one of the most frequent presentations in emergency departments. Imaging has established role in setting of acute trauma with ability to identify potentially fatal conditions. Adequate knowledge of health professionals regarding trauma imaging is vital for improved healthcare. In this work we try to assess knowledge of medical students regarding imaging in trauma as well as identify most effective way of imparting radiology education. Method: This cross-sectional pilot study was conducted at Aga Khan University Medical College & Khyber Girls Medical College, to assess knowledge of medical students regarding imaging protocols practiced in initial management of trauma patients. Results: Only 40 & 20 % respectively were able to identify radiographs included in trauma series. Very few had knowledge of correct indication for Focused abdominal sonography in trauma. Clinical radiology rotation was reported as best way of learning radiology. Conclusion: Change in curricula & restructuring of clinical radiology rotation structure is needed to improve knowledge regarding Trauma imaging.